2019
DOI: 10.1111/jpc.14472
|View full text |Cite
|
Sign up to set email alerts
|

Health needs and timeliness of assessment of Victorian children entering out‐of‐home care: An audit of a multidisciplinary assessment clinic

Abstract: Aim To describe the health needs identified in children attending a comprehensive health assessment at a tertiary hospital, multidisciplinary clinic for children following entry to out‐of‐home care and timeliness of referral and assessment compared with national recommendations. Methods This was a retrospective audit of all the children who attended the Pathway to Good Health clinic at The Royal Children's Hospital, Melbourne from May 2013 until 31 August 2016. Results A total of 119 children aged 0–12 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The largest gap between carer‐perceived need and service use was in mental health, and mental health services were the hardest to access. We know from previous studies that rates of mental health problems and the need for appropriate care are very high 2,4,14 . The limited demographic data about the children described in this study showed that 42% of those in foster care had at least three previous placements, increasing their likelihood of behavioural and mental health problems 27 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The largest gap between carer‐perceived need and service use was in mental health, and mental health services were the hardest to access. We know from previous studies that rates of mental health problems and the need for appropriate care are very high 2,4,14 . The limited demographic data about the children described in this study showed that 42% of those in foster care had at least three previous placements, increasing their likelihood of behavioural and mental health problems 27 .…”
Section: Discussionmentioning
confidence: 63%
“…We know from previous studies that rates of mental health problems and the need for appropriate care are very high. 2,4,14 The limited demographic data about the children described in this study showed that 42% of those in foster care had at least three previous placements, increasing their likelihood of behavioural and mental health problems. 27 The difficulties accessing mental health services existed across metropolitan and regional areas, regardless of carer education level or socio-economic status.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation